Influence of Education Level and Income Level on Public Interest in Paying Zakat at LAZISMU Magelang Central Java Indonesia - Eko Nur Cahyo; Irfan Maulana Ishaq; Adi Rahmannur Ibnu (AL-IKTISAB: Journal of Islamic Economic Law, 2025)
Zakat is one of the obligations in Islam that plays an important role in economic equality and social welfare. However, the level of community compliance in associated with paying zakat is still diverse and is influenced by various factors. This research aims to analyze influence of education level and income level on the interest of the public in paying zakat at LAZISMU Magelang. This research uses a quantitative survey approach through questionnaires distributed to muzakki in LAZISMU Magelang. The analysis technique used is multiple linear regression to test the relationship between the independent variable (education level and income level) and the dependent variable (interest in paying zakat). The results showed that the level of education has a significant influence on interest in paying zakat, where the higher the level of education of a person is, the greater his or her awareness of paying zakat. Moreover, income level affects interest in paying zakat, but in some cases, an increase in income is not always followed by an increase in compliance in paying zakat. This finding shows that in addition to economic factors, religious understanding obtained from education is also a key factor in increasing public participation in zakat payments. Therefore, more intensive zakat education and socialization efforts are needed so that people are more aware of fulfilling their obligations.